Impact of Banditry and Kidnapping on Girl-Child Education in Shiroro Local Government Area of Niger State, Nigeria - Yakubu, Abbas Paiko (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026DO - 10.58709/niujhu.v11i1.2464, 2026)
This study examined the impact of banditry and kidnapping on girl-child education in Shiroro Local Government Area of Niger State. The study was guided by two (2) research questions. The study reviewed related literature under conceptual framework, theoretical framework and empirical studies. The study adopted descriptive research design. The population of the study was three hundred and eighty-nine (389) respondents comprising teachers and pupils in primary schools in Shiroro Local Government Area of Niger State. The sample size of the study totaling two hundred and seventeen (217) was determined using Taro Yamane formula. The instrument used in this study was questionnaire titled: impact of banditry and kidnapping on girl-child education (QEBGCE). Simple percentages, frequency counts, mean and standard deviation were used in data analysis. The findings indicate that the fear of banditry and kidnapping has led to a drastic decline in girl-child enrollment in primary schools in Shiroro Local Government Area. And the impact of banditry and kidnapping on girl-child education are more pronounced in rural areas compared to urban areas, the fear of kidnapping has a greater influence on the educational aspirations of girls in rural areas than in urban areas of Shiroro Local Government Area, The study concluded that frequent disruptions of school academic activities due to the fear of kidnapping was among factors responsible for the decline in girl-child enrollment, hence, there is urgent need to address this critical issue. The study recommended the need for increased security outfit around the schools’ premises to protect girls from bandit attacks and ensure a safe environment for learning activities. Keywords: Banditry, Kidnapping, Girl-child, and education